U.S. monetary policy communication: domestic and international perspectives - Kansoy, Fatih (2019)
This thesis consists of six chapters. Chapter-1 demonstrates the main research motivations and gives a brief of literature review while Chapter-6 presents concluding remarks. Chapter-2 identifies and constructs the surprise components of monetary policy announcements in the US and emphasises the necessity for having two surprise components, namely, the target and path surprise to capture the full extent of monetary policy announcements. Furthermore, this chapter investigates the importance of the event window length on the determination of monetary policy surprises. Chapter-3 explores the effects of FOMC statements on domestic asset prices and exchange rates by considering different times in the US. Using intra-daily and daily dataset from January 1996 to November 2017, this chapter finds that financial markets respond significantly to US monetary policy surprises and different financial assets respond to different factors of the monetary policy surprises. Chapter-4 primarily analyses whether and to what extent the FOMC minutes releases have an impact on the financial markets, as opposed to FOMC statements. Specifically, this chapter finds that the release of FOMC minutes induces “higher than normal” volatility and shows that financial markets respond quickly and significantly to the release of FOMC minutes. Chapter-5 examines the international effects of US monetary policy surprises considering the period before and after the quantitative easing for 56 countries over a 21-year period. It finds that in many countries the effects of spillovers are greater than the domestic impacts in the US.